THE DESIGN OF ASSESSMENT INSTRUMENTS IN ENGLISH RESEARCH - Loly Novita (JEE (Journal of English Education), 2017)
A teacher is to understand and have ability to give assessment to his students since this ability plays a very important role in assessing thelearning evaluation. Teacher is also supposed to know its purpose so that he can find out its functions and which kind of assessment will be designed or developed for his students. In addition, this is useful to give the teacher knowledge about his students’ achievement and how to increase it.